2020
DOI: 10.3390/ani10112004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genotype and Slaughter Age on the Content of Selected Minerals and Fatty Acids in the Longissimus Thoracis Muscle of Crossbred Bulls

Abstract: The aim of this study was to determine the effects of genotype and slaughter age on the mineral content and fatty acid profile of beef. The experiment was performed on 72 crossbred bulls produced by crossing Polish Holstein-Friesian (PHF) cows with bulls of three beef breeds: Hereford (HH), Limousin (LM), and Charolais (CH), slaughtered at 15, 18, and 21 months of age. Samples of the longissimus thoracis muscle were collected to determine their mineral (potassium—K, sodium—Na, magnesium—Mg, zinc—Zn, and iron—F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Gregory et al [ 57 ] pointed out that breed is an important factor in shaping slaughter performance. Comparative studies on the fattening value of PHF, LM, CH, and HH confirmed these reports [ 58 , 59 , 60 ]. Additionally, Sargentini et al [ 61 ] and Humada et al [ 62 ] reported that total SFA content did not significantly alter with increasing slaughter age.…”
Section: Discussionsupporting
confidence: 68%
“…Gregory et al [ 57 ] pointed out that breed is an important factor in shaping slaughter performance. Comparative studies on the fattening value of PHF, LM, CH, and HH confirmed these reports [ 58 , 59 , 60 ]. Additionally, Sargentini et al [ 61 ] and Humada et al [ 62 ] reported that total SFA content did not significantly alter with increasing slaughter age.…”
Section: Discussionsupporting
confidence: 68%
“…The content of saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs) increases faster with increasing fatness than the content of PUFAs, resulting in a decrease in the relative proportion of PUFAs and, consequently, in the polyunsaturated‐to‐saturated fatty acid (PUFA/SFA) ratio (Andreo et al., 2016). There are some reports regarding the fatty acid composition for bulls, steers, or heifers of Polish Holstein Friesian × Limousine crossbreds (Momot et al., 2017, 2020; Nogalski et al., 2014; Solarczyk et al., 2020), while only few evaluated of four different adipose tissues (Sobczuk‐Szul et al., 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetic strategies, aging has become a viable technique for improving the sensory attributes of meat because tenderization occurs over time, making the meat more tender after slaughter ( Monteiro et al, 2022 ). Momot et al (2020) determined the effects of bovine genotype and slaughter age on the mineral content and fatty acid profile of meat. The results showed that the intramuscular fat content of the longissimus thoracis muscle increased by up to 1.80% with age.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the intramuscular fat content of the longissimus thoracis muscle increased by up to 1.80% with age. The slaughter age significantly affected the concentrations of saturated, monounsaturated, and unsaturated fatty acids as well as the monounsaturated/saturated fatty acid ratio in bull longissimus thoracis muscles ( Momot et al, 2020 ). Table 1 summarizes the approaches used to obtain healthier meat.…”
Section: Resultsmentioning
confidence: 99%